Synthetic self-adjuvanting glycopeptide cancer vaccines - McDonald, David M.; Byrne, Scott N.; Payne, Richard J. (Frontiers in Chemistry, 2015)
Due to changes in glycosyltransferase expression during tumorigenesis, the glycoproteins of cancer cells often carry highly truncated carbohydrate chains compared to those on healthy cells. These glycans are known as tumor-associated carbohydrate antigens, and are prime targets for use in vaccines for the prevention and treatment of cancer. Herein, we review the state-of-the-art in targeting the immune system towards tumor-associated glycopeptide antigens via synthetic self adjuvanting vaccines, in which the antigenic and adjuvanting moieties of the vaccines are present in the same molecule. The majority of the self-adjuvanting glycopeptide cancer vaccines reported to date employ antigens from mucin 1, a protein which is highly over-expressed and aberrantly glycosylated in many forms of cancer. The adjuvants used in these vaccines predominantly include lipopeptide- or lipoamino acid-based TLR2 agonists, although studies investigating stimulation of TLR9 and TLR4 are also discussed. Most of these adjuvants are highly lipophilic, and, upon conjugation to antigenic peptides, provide amphiphilic vaccine molecules. The amphiphilic nature of these vaccine constructs can lead to the formation of higher-order structures by vaccines in solution, which are likely to be important for their efficacy in vivo.